Grounded theory: An illustrative application in the Portuguese footwear industry - Mónica Monteiro; Álvaro Rosa; Adelaide Martins; Shital Jayantilal (Administrative Sciences, 2023)
Grounded theory is an inductive research methodology aiming at the construction of new concepts or new theories able to explain emerging phenomena. The objective of this paper is to provide insights on the usage of grounded theory in management research. We showcase how grounded theory can bring light to development modes of Portuguese small and medium-sized enterprises (SME) in the specific reality of the footwear industry, where a changing and unpredictable environment threatens constant loss of competitive advantage. An interpretive-epistemological research philosophy was adopted, and evidence was gathered through nine semi-structured interviews. Portugal is currently a reference in the international footwear market and the sustainability of the sector plays an important role in the Portuguese industrial structure. This study highlights how the method of grounded theory can add value to research by uncovering complex managerial realities and develop new questions and issues for theory building.
Keywords: 350; innovation; dynamic capabilities; grounded theory; internationalization; market change